On Why Music Changes What (We Think) We Taste. (April 2013) - Spence, Charles; Deroy, Ophelia
A pair of recently published studies demonstrate that what we happen to be listening to can sometimes change our perception (or, at the very least, our rating) of what we are eating or drinking. In one recent study, North (2012) showed that the emotional attributes (or connotation) of a piece of music could influence people's perception of red or white wine. Meanwhile, Crisinel et al. (2012) reported that listening to a lower-pitched soundscape can help to emphasize the bitter notes in a bittersweet toffee while listening to a soundscape with a higher pitch tends to bring out its sweetness. Although the most appropriate psychological and neuroscientific explanations for such crossmodal effects are still uncertain, we outline a number of possible alternatives for such intriguing, not to mention surprising, phenomena.